Evaluation of women’s aging influence on sperm passage inside the fallopian tube using 3D dynamic mechanical modeling - Nassir, Mayssam; Levi, Mattan; Wiser, Amir; Shaked, Natan T. (Frontiers in Bioengineering and Biotechnology, 2024)
The fallopian tubes play an important role in human fertility by facilitating the spermatozoa passage to the oocyte as well as later actively facilitating the fertilized oocyte transportation to the uterus cavity. The fallopian tubes undergo changes involving biological, physical, and morphological processes due to women aging, which may impair fertility. Here, we have modelled fallopian tubes of women at different ages and evaluated the chances of normal and pathological sperm cells reaching the fertilization site, the ampulla. For this purpose, we present a dynamic three-dimensional (3D) mechanical model of human sperm cells swimming through the human fallopian tube for different women's age groups. By utilizing a unique combination of simulative tools, we implemented dynamic 3D detailed geometrical models of many normal and pathological sperm cells swimming together in 3D geometrical models of three fallopian tubes describing different women's age groups. By tracking the sperm cell swim, we found that for all age groups, the quantity of normal sperm cells in the ampulla is the highest, compared with the pathological sperm cells. On the other hand, the number of normal sperm cells in the fertilization site decreases due to the morphological and mechanical changes that occur in the fallopian tube with age. Moreover, in older ages, the normal sperm cells swim with lower velocities and for shorter distances inside the ampulla toward the ovary. Thus, the changes that the human fallopian tube undergoes due to women's aging have a significant influence on the human sperm cell motility. Our model of sperm cell motility through the fallopian tube in relation to the woman's age morphological changes provides a new scope for the investigation and treatment of diseases and infertility cases associated with aging, as well as a potential personalized medicine tool for evaluating the chances of a natural fertilization per specific features of the man's sperm and the woman's reproductive system.